Microstructure and anti-oxidation properties of Yb2Si2O7/SiC bilayer coating for C/SiC composites. Issue 18 (15th December 2019) - Chen, Pengju; Pan, Ling; Xiao, Peng; Li, Zhuan; Pu, Dongmei; Li, Jinwei; Pang, Liang; Li, Yang
Abstract: A Yb2 Si2 O7 /SiC bilayer anti-oxidation coating was fabricated on the surface of C/SiC composites by the chemical vapor deposition (CVD) and the combination of sol-gel and air spraying method to enhance the oxidation resistance of C/SiC composites. Results indicated that the bilayer coating can efficiently prevent the oxidation of C/SiC composites in ambient air at 1773 K for more than 100 h with slight weight loss rate of 8.12 × 10 -5  g cm -2  h -1 and retained compression strength of 96.78%. Microstructure characterization revealed that the gradual densification of Yb2 Si2 O7 outer coating exposed to 1773 K reduced the oxygen diffusion pathes within the Yb2 Si2 O7 /SiC bilayer coating, therefore, the weight loss rate of specimens decreased as oxidation proceeded. The oxidation activation energy of bilayer coating coated C/SiC specimen was 107.73 kJ/mol during long time oxidation within the temperature range from 1573 K to 1773 K. Based on the microstructure analysis and oxidation behavior of the specimens with different exposure time of oxidation, the oxygen diffusion rate in the bilayer coating was the controlling link during the long time oxidation course.